2005
DOI: 10.1016/s0899-3467(07)60107-4
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Perceptions of Emotions Associated with Pain: A Survey

Abstract: This study found that a substantial number (80-90%) of the chiropractors surveyed believe that emotional factors influence pain syndromes. However, less than half of these practitioners report that they are able to evaluate emotional factors and approximately only a third report that they are able to treat them. This study shows there is a need for further research of chiropractors to be able to evaluate emotional factors and techniques that can be used to rectify emotional components of their patients' pain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Diversified technique was reported to be the most commonly used technique system amongst Australian chiropractors. The high frequency of use of Diversified technique is in line with previous studies from Australia and overseas [4][5][6]13,26]. A Canadian study from 2009 found that Diversified was the main technique used in private practice, followed by Activator and Thompson technique [14].…”
Section: Scope Of Practicesupporting
confidence: 81%
See 1 more Smart Citation
“…Diversified technique was reported to be the most commonly used technique system amongst Australian chiropractors. The high frequency of use of Diversified technique is in line with previous studies from Australia and overseas [4][5][6]13,26]. A Canadian study from 2009 found that Diversified was the main technique used in private practice, followed by Activator and Thompson technique [14].…”
Section: Scope Of Practicesupporting
confidence: 81%
“…However, data regarding the prevalence of specific musculoskeletal conditions presenting to chiropractic practices is lacking. There is some data available regarding presenting symptomatic regions [7,26,33], but not related to specific musculoskeletal diagnoses. Therefore, selection of musculoskeletal conditions based on specific epidemiological data was not possible.…”
Section: Limitationsmentioning
confidence: 99%
“…Diversified technique was reported to be the most commonly used technique system amongst Australian chiropractors. The high frequency of use of Diversified technique is in line with previous studies from Australia and overseas [ 4 - 6 , 13 , 26 ]. A Canadian study from 2009 found that Diversified was the main technique used in private practice, followed by Activator and Thompson technique [ 14 ].…”
Section: Discussionsupporting
confidence: 85%
“…11,12,15,21 Many studies on the knowledge, beliefs, and attitudes toward CP have been conducted in Canada among health care professionals (e.g., nurses, physicians, pharmacists, physiotherapists, etc.) 2,[22][23][24][25][26][27][28][29][30][31] or patients. [32][33][34][35][36] Understanding the beliefs and attitudes of the general population as a whole is also important and can permit better designing and tailoring of education programs, awareness campaigns and stigma reduction activities.…”
Section: Introductionmentioning
confidence: 99%